Competition dynamics of Parthenium hysterophorus in direct-seeded aerobic rice fields. (20th April 2020) - Bajwa, Ali A.; Ullah, Aman; Farooq, Muhammad; Chauhan, Bhagirath S.; Adkins, Steve
Abstract: Parthenium hysterophorus is a prolific invasive weed species, which infests many crops in over 40 countries around the world. A 2-year field study was carried out to quantify the potential impacts of this weed on direct-seeded rice. Parthenium weed was allowed to compete for 2, 4, 6 or 8 weeks after crop emergence, while full season weedy and weed-free plots were maintained as controls. Parthenium weed plants grew taller and attained more biomass as the competition duration prolonged. The yield and yield-related attributes of rice were negatively affected with increasing competition duration. The season-long competition caused the highest reductions in panicle number (28–34%), panicle length (26–27%), grains per panicle (22–23%) and grain yield (33 and 38%) of rice in both years. Weed competition for 2–8 weeks caused 5–34% and 6–33% losses in rice grain yield during both years, respectively. Importantly, Parthenium weed control after 8 weeks of competition did not improve rice yield significantly. The results suggested that Parthenium weed should be controlled in rice fields between 4 and 8 weeks after crop emergence under direct-seeded conditions to avoid over 10% yield losses.